Human Flourishing and Sustainable Success: A Human-Centric Approach to Corporate Growth - De Molli, Federica (Journal of Positive Management, 2026)
Purpose: This article explores how human flourishing can be understood as an organizational capability that supports sustainable success, rather than solely as an individual psychological outcome. It aims to integrate insights from positive psychology, leadership, and organizational studies into a coherent human-centric framework. Design/methodology/approach: The article adopts a conceptual research design grounded in an interdisciplinary review of literature. To enrich and illustrate the proposed framework, it draws on qualitative insights from in-depth interviews with three senior executives operating in highly competitive global industries. These insights are used illustratively rather than for empirical generalization. Findings: The article develops an integrative framework identifying three interrelated levers that enable flourishing-oriented organizations: values-based leadership, organizational cultures fostering psychological safety, creativity, and belonging, and the strategic embedding of well-being into everyday organizational practices. Together, these levers link human flourishing to long-term organizational resilience, innovation, and meaningful performance. Implications/limitations: The study offers practical implications for leaders seeking to move beyond short-term performance metrics toward more sustainable, human-centric models of success. As a conceptual article supported by illustrative qualitative insights, its main limitation lies in the absence of large-scale empirical testing, which opens avenues for future research. Originality/value: The article contributes to positive management scholarship by reframing human flourishing as a collective organizational capability and by clarifying the mechanisms through which leadership and culture connect flourishing to sustainable success. Keywords: human flourishing, sustainable success, values-based leadership, organizational culture, well-being, positive management